(untitled) (Research, Society and Development, 2022)
Diabetes mellitus is a chronic metabolic disease that has increased significantly in the world in recent years. The lack of knowledge, associated with poor eating habits and lifestyle of individuals are factors that favor the development of type 2 diabetes mellitus (DM2). Therefore, the objective of the study was to verify the knowledge of individuals from rural areas about DM2. The sample consisted of 200 individuals of both sexes aged 18 years or over, rural residents. A semi-structured questionnaire was applied on the participants’ sociodemographic data, knowledge and behaviors related to DM2. The results showed that 66.5% of respondents were unaware of the disease and that 40.2% of women were overweight and 38.6% were obese, constituting potential risk groups. Of the total number of participants, 16.5% had DM2. Therefore, it was concluded that health education actions are necessary as a strategy to ensure a better quality of life for the population.